The Urgency of Community Service Punishment as an Alternative to Imprisonment in the Perspective of National Criminal Law Reform - Avvy Olivia Atam; Hery Chariansyah (Jurnal Kewarganegaraan, 2026)
Community service punishment is an important instrument of Indonesia’s criminal law reform, reflecting a shift from imprisonment-oriented sentencing toward a more selective, proportional, and socially reintegrative penal model. This article examines the regulation of community service punishment under Law Number 1 of 2023 concerning the Indonesian Criminal Code and formulates an ideal model for its implementation within the Indonesian sentencing system. This study applies normative legal research using statutory, conceptual, limited comparative, and criminal policy approaches. The findings indicate that community service punishment is positioned as a principal punishment that functions as an alternative to short-term imprisonment and light fines. This regulation demonstrates the legislature’s effort to introduce a form of punishment that does not always rely on deprivation of liberty, while still maintaining criminal accountability. Nevertheless, its effectiveness depends on the availability of sentencing guidelines, individual assessment, supervision, probation guidance, standardized community work, and compliance evaluation. This article proposes an implementation model based on operational legal rules, judicial sentencing guidelines, offender assessment, protection of human dignity, integrated supervision, and measured community involvement.